Individual Interest and Political Legitimacy - Dietrich, Frank; Justus Liebig University Giessen (My University, 2009)
Criticism of contract theory has always played an important role in Hartmut Kliemt's writings on political philosophy. Notwithstanding his objections to a consent-based justification of the state he has never subscribed to an anarchist position. In Hartmut Kliemt's view, a minimal state which protects the basic liberties of its citizens has to be considered legitimate. The article begins with a brief restatement of the most influential objections that have been raised against the various forms of contract theory. Thereafter interestbased accounts of political legitimacy are critically examined; it is argued that individual interests fail to provide a justification for any kind of political authority. Finally, philosophical anarchism is suggested as a possible alternative to contract theory and interest theory. Although philosophical anarchism holds that no state has a moral right to rule, it can be reconciled with the view that it is in the individual's interest to create and maintain a minimal state.
Keywords: ddc:100; ddc:330